Ukraine Science, Technology, and Innovation Public Expenditure Analysis - World Bank (World Bank, Washington, DC, 2017)
This report is one of four analytical pieces on Ukraine’s innovation and entrepreneurial ecosystem developed by the World Bank’s Ukraine Technical Assistance on Innovation, supported by the Swedish Ukraine Financial and Enterprise Sector Recovery and Growth Trust Fund. This report evaluates the quality mix of public support programs for science, technology, and innovation (STI) in Ukraine and provides recommendations for the improvement of the public support programs’ effectiveness. The evaluation aims to determine the coherence in the allocation of STI expenditures in addressing the main innovation challenges in the country, as well as the main gaps and redundancies. The objective of the review is to increase the efficiency and effectiveness of STI public expenditure and maximize impact. The methodology used builds upon the Public Expenditure Reviews (PER) for STI (Correa 2014) and compares the demand for innovation policies arising from an innovation ecosystem diagnostic with the actual expenditure on STI. Given the lack of budget programming, STI expenditure sourced from the BOOST database only approximates actual expenditure due to the lack of budget codes for all STI-related expenditure. The fact that most expenditure is disbursed as block funding reduced the granularity of the analysis. The analysis uncovered significant gaps related to STI policies and revealed general trends in STI expenditure.